Effect of La3+ Substitution at Bi-Site on Transport Properties of Bi0.3-xLaxPr0.3Ca0.4Mn0.1Cr0.9MnO3 - Ibrahim, Norazila; Asmira Amaran, Nor; Mohamed, Zakiah; Kamal Yahya, Ahmad (International Journal of Engineering and Technology, 2019)
Magnetic and electronic transport properties of Bi0.3-xLaxPr0.3Ca0.4Mn0.1Cr0.9O3 (0â‰¤xâ‰¤0.2) manganites have been investigated by measurements of AC-susceptibility, resistivity and magnetoresistance. The samples were prepared using conventional solid-state synthesis method. Magnetic susceptibility versus temperature measurements showed all samples exhibit ferromagnetic to paramagnetic transition with Curie temperature, Tc enhanced from 111 K (x=0) to 174 K (x=0.2). Electrical resistivity measurements of the samples in zero field showed increase of metal-insulator (MI) transition temperature from 58 K(x=0) to 88 K(x=0.2). The increase in both Tc and TMI indicates enhancement of double exchange (DE) interaction involving Mn3+ and Mn4+ ions as a result of weakening of the hybridization effect between Bi3+ 6s2 lone pair with O orbital due to La3+ substitution.Â La substitution in the Bi-based compound is suggested reduce MnO6 octahedral distortion hence increasing delocalization of charge carriers. The observed variation in MR behavior due to La substitution indicates the substitution influence the MR mechanism of extrinsic and intrinsic behavior in Bi0.3-xLaxPr0.3Ca0.4Mn0.1Cr0.9O3 .Â